Rare manifestation of orbital hematoma in hemophilia B: A case report - Jimanto, Vincent; Ritonga, Dwi Herawati (Buletin Kedokteran & Kesehatan Prima, 2025)
Introduction: Severe Hemophilia B is a blood coagulation disorder with the most common clinical manifestation is bleeding manifestation in major joint. In this article, we present a case of 5-year-old boy with severe hemophilia B, whose clinical bleeding manifestation was rarely reported, located in unilateral orbital hematoma. By reporting this case of hemophilia B with rare clinical manifestations, we aim to increase the awareness so as to accelerate the diagnosis and management of hemophilia B. Case Presentation: A 5-year-old boy came to the emergency ward with complaints of a swollen and bluish right eye socket since a week prior to admission. Patient also experienced other symptoms such as frequent joint pain, prolonged bleeding after injury, and bruises (hematoma) on the trunk, elbows, and knees. The coagulation tests showed a prolonged APTT with normal PT and INR. Due to resource-limited setting, sample referral was needed to perform factor VIII and IX examination, and FFP transfusion was given to the patients during the admission. Factor VIII and IX results were available after patient had been discharged, with a low-level activity of factor IX (<1%). Patient was diagnosed as severe hemophilia B, and was referred to tertiary health-care facility from outpatient department for comprehensive management. Conclusion: Despite of the most common location of bleeding manifestation in Hemophilia B, other bleeding manifestation such as orbital hematoma should also be considered as Hemophilia B manifestation. Early diagnosis and prompt treatment will give a better prognosis for patient with hemophilia.